2015
DOI: 10.3109/14767058.2015.1041493
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early caffeine on neurodevelopmental outcome of very low-birth weight newborns

Abstract: Early caffeine therapy was associated with better BSID III scores in a cohort of VLBW newborns. Newborns with acute chorioamnionitis benefited from early caffeine therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
2
18
1
Order By: Relevance
“…The search found 4066 studies and 14 were included in the current review. These comprised six cohort studies and eight randomized controlled trials (RCTs) (Figure ). The cohort studies included a total of 63 075 neonates with gestational age ranging from 23 to 33 weeks and birth weight between 410 and 2060 g. In the RCTs, a total of 1363 neonates were enrolled with mean gestational age of 26.3 to 32.0 weeks and mean birth weight between 872 and 1800 g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search found 4066 studies and 14 were included in the current review. These comprised six cohort studies and eight randomized controlled trials (RCTs) (Figure ). The cohort studies included a total of 63 075 neonates with gestational age ranging from 23 to 33 weeks and birth weight between 410 and 2060 g. In the RCTs, a total of 1363 neonates were enrolled with mean gestational age of 26.3 to 32.0 weeks and mean birth weight between 872 and 1800 g.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies evaluated the use of early vs. late caffeine therapy and three studies assessed early caffeine use vs. placebo . In the remaining four studies, one study each examined: the effects of early caffeine use only , early high‐dose caffeine vs. early standard‐dose caffeine , early caffeine (<2 h after birth) vs. routine caffeine (≥12 h after birth) and caffeine vs. theophylline .…”
Section: Resultsmentioning
confidence: 99%
“…38 Several retrospective cohort studies subsequently observed that earlier initiation of caffeine therapy at <3 days was associated with improved outcomes as compared to initiation at ≥3 days ( Table 2). 24,[84][85][86][87] The largest of these studies evaluated outcomes in 62,056 VLBW infants and compared the outcomes between infants receiving early caffeine therapy at <3 days and infants not started on caffeine therapy until ≥3 days. 24 Early caffeine therapy was associated with a lower incidence of BPD (23.1% vs. 30.7%, p < 0.001), less treatment of PDA (12.3% vs. 19%, p < 0.001), lower incidence of intraventricular hemorrhage (29.4% vs. 32.7%, p < 0.001), and less therapy for ROP (2.8% vs. 5%, p < 0.001).…”
Section: Timing Of Caffeine Initiation: Benefits Of Early Treatmentmentioning
confidence: 99%
“…Several studies have compared outcomes after early caffeine initiated in the first two days of life to later caffeine initiated after the third day of life. A meta‐analysis of these studies suggested that the earlier use of caffeine resulted in a decreased incidence of several morbidities of prematurity, including death, BPD, composite outcome of death, ROP requiring laser treatment, surgically treated patent ductus arteriosus, IVH and periventricular leukomalacia and a shorter duration of mechanical ventilation . Therefore, it would be important to study the optimal timing of a higher dose caffeine to improve both the neurodevelopmental outcomes and the short‐term outcomes in VLBW infants.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that the caffeine therapy improved the neurodevelopmental outcomes, which could have been related to improvement in the respiratory outcomes (3). A previous study by our group showed that early initiation of caffeine, within the first 48 hours after birth, may have be associated with improved neurodevelopmental outcomes in very low birth weight (VLBW) infants (4). There has been an increasing trend to use caffeine within the first 48 hours of birth and the results have shown improved short-term outcomes in VLBW infants (5)(6)(7).…”
Section: Introductionmentioning
confidence: 91%